A carbon / carbon heater for single crystal thermal field and its preparation method

By using prefabricated bodies with carbon cloth and mesh fabric structures for vapor deposition and machining, the problem of poor density uniformity of traditional heaters is solved, and a carbon/carbon heater with uniform density, excellent heat conduction performance and long service life is achieved.

CN119751106APending Publication Date: 2025-04-04SHAANXI MEILAND NEW MATERIALS CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411971757.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The density uniformity of traditional carbon/carbon heaters during the density enhancement process leads to unevenness in the internal structure and performance of the heater, affecting the heat distribution and heating efficiency.

Method used

A prefabricated body made of the intermediate carbon cloth and several mesh cloths symmetrically arranged on both sides of the carbon cloth is formed by vapor deposition and machining and refining to form a carbon/carbon heater with uniform density.

Benefits of technology

It improves the uniformity of the finished product density, enhances the heat conduction performance, extends the service life of the heater, and is not easy to crust and has a more uniform density distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751106A_ABST
    Figure CN119751106A_ABST
Patent Text Reader

Abstract

The present application relates to the field of new materials, and specifically discloses a carbon / carbon heater for a single crystal thermal field and a preparation method thereof. The preparation method comprises the following steps: S1, selecting a preform made of a mesh cloth and a carbon cloth to cut and form a heater blank, wherein the preform is made of a layer of carbon cloth and a plurality of mesh cloths symmetrically arranged on both sides of the carbon cloth; S2, vapor-depositing the heater blank prepared in step S2, during which current is passed through the heater blank so that the center temperature of the mesh cloth of the heater blank reaches 1000-1100°C, and the deposition is terminated after 100-200 hours, and the density of the heater blank is ≥1.6g / cm 3 ; S3. Fine machining to obtain a carbon / carbon heater; The present application also discloses a carbon / carbon heater for a single crystal thermal field obtained by the above method. The present application has the characteristics of obtaining a carbon / carbon heater with a more uniform finished product density so as to have better thermal conductivity performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new materials, and more specifically, to a carbon / carbon heater for a single crystal thermal field and a preparation method thereof. Background Art

[0002] The Czochralski single crystal furnace is a device that uses a heater to melt polycrystalline materials such as polysilicon in an inert gas environment and grow dislocation-free single crystals using the Czochralski method. As a key device for the preparation of semiconductor materials, the core of the Czochralski single crystal furnace is to provide a stable and suitable thermal environment to promote the melting of polycrystalline materials and the growth of single crystals. The heater is also the core component of the thermal field of the single crystal furnace, which increases the thermal energy of polycrystalline melting and crystal growth. Traditional heaters are made of graphite, but graphite has poor thermal shock resistance and poor mechanical properties, which shortens its service life and affects normal use.

[0003] With the development of the industry and new materials, carbon / carbon heaters are gradually used as the main heating method in large-sized CZ silicon single crystal furnaces, which have the advantages of good thermal shock resistance and easy preparation of complex large-sized structures. Patents such as CN101386547B, CN117510219A, CN104710184A, CN108975922B and CN117586037A disclose methods for preparing carbon / carbon composite materials, all of which adopt traditional methods for preparing carbon / carbon composite materials, i.e., using carbon cloth + mesh tire needle puncture, deposition densification, impregnation and processing procedures. However, the densification uniformity is not good when the above traditional methods are used, which will lead to uneven internal structure and performance of the heater, and subsequently affect the heat distribution and heating efficiency of the heater.

[0004] Therefore, it is necessary to provide a new preparation method to obtain a carbon / carbon heater with a more uniform finished product density so as to have better thermal conductivity. Summary of the invention

[0005] In order to improve the density uniformity of the finished product, the present application provides a carbon / carbon heater for a single crystal thermal field and a preparation method thereof.

[0006] In a first aspect, the present application provides a method for preparing a carbon / carbon heater for a single crystal thermal field, using the following technical solution: A method for preparing a carbon / carbon heater for a single crystal thermal field comprises the following steps: S1, cutting a preform made of a mesh cloth and a carbon cloth to form a heater blank, wherein the preform is made of a layer of carbon cloth and a plurality of mesh cloths symmetrically arranged on both sides of the carbon cloth; S2, vapor deposition is performed on the heater blank prepared in step S2, and current is passed through the heater blank during the vapor deposition process, so that the center temperature of the mesh cloth of the heater blank reaches 1000-1100°C, and the deposition is completed after 100-200 hours, and the density of the heater blank is ≥1.6g / cm 3 ; S3. Machining and finishing the heater blank after vapor deposition to obtain a carbon / carbon heater.

[0007] By adopting the above-mentioned technical scheme, the preform in the present application is made of a middle carbon cloth and a plurality of mesh cloths symmetrically arranged on both sides of the carbon cloth, thus forming an A / … / A / B / A / … / A structure, wherein A is a mesh layer formed by the mesh cloth, and B is a carbon cloth layer formed by the carbon cloth. Compared with the traditional structure in which the carbon cloth and the mesh cloth are directly needle-punched and compounded, the preform in the present application has a larger pore structure, which is convenient for densification. At the same time, in the traditional structure, the carbon fibers are arranged in a specific direction, while the carbon fibers in the mesh cloth are randomly distributed. In the present application, a large amount of mesh cloth structure is used, and the orientation of the carbon fibers in the preform is weakened. The density is more uniform during the subsequent deposition and densification process, thereby avoiding the problem of uneven density distribution caused by excessive orientation of the carbon fibers.

[0008] In addition, the present application also combines the E-CVI method, and current is passed through the preform during the vapor deposition process, so that a certain temperature gradient can be generated inside the preform, that is, the inner temperature is high and the outer temperature is low. In this way, the interior of the preform is preferentially deposited. As the deposition density increases, the preform deposition gradually grows from the inside to the outside to the final density. Not only is the deposition densification effect higher, but the finished product density is also higher and the density distribution is more uniform. Finally, the method provided in the present application has a fast densification speed, and the density is ≥1.6g / cm after 100-200h of deposition. 3 ; A high-density carbon / carbon product is obtained, and the deposit is not easy to crust. The density difference coefficient at different positions is less than 2%, and the density distribution is more uniform. The carbon / carbon heater made in this way heats more evenly, and the deposited carbon is denser, and the service life of the heater is longer.

[0009] Optionally, the number of layers of the web fabric in step S1 is 2-10.

[0010] Optionally, the surface density of the mesh fabric in step S1 is 70-150 g / m 2 , the surface density of carbon cloth is 200-350g / m 2 .

[0011] Optionally, the density of the preform in step S1 is 0.15-0.25 g / m 3 .

[0012] By adopting the above technical solution, the overall performance of deposition densification effect and density distribution uniformity is better by controlling the number of mesh cloth layers, mesh cloth and carbon cloth surface density. Controlling the number of mesh cloth layers adjusts the distribution of pore structure in the preform, thereby affecting the final densification effect, while moderate surface density of mesh cloth and carbon cloth helps to improve carbonization efficiency while having better density distribution uniformity.

[0013] Optionally, the vapor deposition parameters in step S2 are: natural gas as the precursor, nitrogen as the dilution gas, the temperature in the deposition furnace is 800-900°C, and the nitrogen flow rate is 0.1-1m 3 / h, natural gas flow rate is 0.1-1m 3 / h, the deposition time is 100-200h.

[0014] By adopting the above technical solution and combining the deposition densification system in this application with the preform setting, the product density can be ≥1.6g / cm after 100-200h of deposition in this application. 3 Compared with the traditional isothermal CVI deposition, the density is only 1.0g / cm 3 The deposition efficiency of the present application is higher than that of the heater prepared by traditional E-CVI and CVI densification. During the densification process, a better thermal gradient is formed inside and outside the preform, and the deposition is from the inside to the outside. The deposition is not easy to form a crust, and the speed is faster and more uniform.

[0015] Optionally, in step S1, the preform is made by connecting the web cloth and the carbon cloth, and the web cloth and the web cloth by needle punching.

[0016] By adopting the above technical solution, when needle punching is used for compounding, a strong mechanical bonding force is formed by the mutual interlacing and locking between the fibers, so that the preform has a higher composite strength.

[0017] Optionally, in step S1, modified phenolic resin is sprayed on the mesh cloth and carbon cloth, and between the mesh cloth and the mesh cloth of the preform during the needling compounding, and baking is performed after the needling compounding is completed.

[0018] By adopting the above technical solution, the fibers of the mesh cloth are distributed more loosely, and the gaps between the fibers are larger. When the needle is combined with the needle, it is easier to cause damage to the fibers when penetrating, such as fiber breakage, deformation, and pulling out. On the one hand, the damage to the fibers will lead to uneven adhesion of the deposited materials on the fiber surface during the vapor deposition process, especially when the fibers are broken or pulled out, an uneven surface will be formed, thereby affecting the uniformity of the deposition layer, and the deformation of the fibers will also change the spatial distribution between the fibers, thereby affecting the penetration and deposition of the deposited materials in the fiber gaps, and ultimately affecting the uniformity of the vapor deposition. On the other hand, the damage to the fibers will also affect the overall structural strength of the preform and the interlayer bonding strength.

[0019] Therefore, modified phenolic resin is also sprayed during the needle-punching composite process in the present application, so that the phenolic resin fills the pores and defects inside the preform, making the structure denser. This dense structure is conducive to the uniform deposition of carbon atoms during vapor deposition, reducing the influence of pores and defects on deposition uniformity, especially the combination of needle-punching composite and phenolic resin in the present application, which not only retains the pore structure brought by the mesh cloth and the random distribution advantages of carbon fibers, but also reduces the deformation of fibers during the needle-punching process through the filling effect of the resin, and promotes the uniform penetration of carbon atoms through the random distribution and larger pore structure of the mesh cloth, further improving the deposition uniformity, and also retains the improvement in mechanical strength brought by needle-punching composite. Finally, in the deposition densification process, carbon atoms can penetrate into various parts of the preform more evenly, thereby forming a carbon-carbon heater with more uniform density and better performance.

[0020] Optionally, the modified phenolic resin is prepared by mixing the following raw materials in parts by weight: 10-20 parts of phenolic resin, 3-5 parts of mesophase asphalt, 1-3 parts of silane coupling agent, 2-5 parts of sucrose or glucose, and 0.5-1.2 parts of trioxymethylene.

[0021] By adopting the above-mentioned technical scheme, the modified phenolic resin in the present application is prepared by modifying the intermediate phase asphalt, sucrose or glucose and tripolyformaldehyde. The intermediate phase asphalt contains rich double bonds and aromatic groups. Under the action of tripolyformaldehyde as a cross-linking agent, it can form a cross-linked structure with the phenolic resin, thereby improving the residual carbon rate and high temperature resistance of the phenolic resin. In this way, during the subsequent deposition, on the one hand, the fiber breakage and deformation of the mesh cloth during high-temperature deposition can be improved, thereby alleviating the influence of fiber damage on the deposition uniformity. On the other hand, a higher residual carbon rate can also form a denser structure during the curing process, reduce the formation of pores and defects, and help provide a better substrate during the vapor deposition process, so that the deposition is more uniform, forming a continuous and uniform deposition, and finally the density uniformity of the heater is better.

[0022] In addition, the addition of sucrose or glucose can be dispersed between the pores of the mesh cloth. On the one hand, it has a certain limiting effect on the fibers, reducing breakage or deformation during the needle punching process. On the other hand, it forms carbonaceous materials during the deposition process, which on the one hand enhances the mechanical properties of the overall material, and on the other hand, it can also form a more uniform and dense deposition layer during the vapor deposition process. Moreover, the volume vacancies formed after carbonization are more conducive to the vapor deposition. Ultimately, the densification deposition efficiency of the heater is faster and has higher deposition uniformity.

[0023] Optionally, the modified phenolic resin is prepared by the following method: After mixing the phenolic resin and the silane coupling agent, the temperature is raised to 150-160° C., and then the mesophase asphalt and trioxymethylene are added. After stirring for 20-30 minutes, the temperature is lowered to 80-90° C., and then sucrose or glucose is added and mixed to obtain the modified phenolic resin.

[0024] Optionally, 1-3 parts by weight of Peek are added together with sucrose or glucose.

[0025] By adopting the above technical solution, Peek has extremely high heat resistance stability, and Peek modified phenolic resin has better heat resistance, which has a certain protective effect on the mesh cloth fibers, helping them to maintain a certain structural stability in the high temperature environment of vapor deposition, and reducing the distribution uniformity caused by damage such as fiber breakage, thereby helping to achieve uniform temperature distribution. It also has better adhesion between the mesh cloth and carbon cloth, better stability and density, which helps to evenly distribute the gas flow and achieve more uniform deposition.

[0026] Optionally, the preform preparation in step S1 specifically includes the following steps: The mesh cloth and the carbon cloth are stacked and then needle-punched for compounding. During the needle-punching process, a resin solution mixed with modified phenolic resin and ethanol in a mass ratio of 1: (8-10) is sprayed. After the needle-punching, the preform is dried at 120-150° C. to obtain a preform.

[0027] In a second aspect, the present application provides a carbon / carbon heater for a single crystal thermal field, which adopts the following technical solution: A carbon / carbon heater for a single crystal thermal field is prepared by the preparation method.

[0028] By adopting the above technical scheme, the density distribution of the carbon / carbon heater obtained by the preparation method provided in the present application is more uniform, and the density is>1.6, the deposition is not easy to form a crust, and the density difference coefficient of different positions of the product is <2%; in addition, the method provided in the present application first cuts to obtain the heater blank and then performs vapor deposition, which is closer to the final product size and has a higher material utilization rate. In addition, the sandwich structure is combined with the E-CVI process in the present application, and a better thermal gradient is formed inside and outside the preform during the densification process. The deposition is from the inside to the outside, the deposition is not easy to form a crust, and the speed is faster and more uniform. Finally, the finished heater has more uniform heat generation, and the deposited carbon is denser, and the heater has a longer service life.

[0029] In summary, this application has the following beneficial effects: 1. The preform in the present application is made of a carbon cloth in the middle and a plurality of mesh fabrics symmetrically arranged on both sides of the carbon cloth, so as to form an A / … / A / B / A / … / A structure, wherein A is a mesh layer formed by the mesh fabric, and B is a carbon cloth layer formed by the carbon cloth. Compared with the conventional structure obtained by directly needle-punching the carbon cloth and the mesh fabric, the preform in the present application has a larger pore structure, which is convenient for densification. At the same time, in the conventional structure, the carbon fibers are arranged in a specific direction, while the carbon fibers in the mesh fabric are randomly distributed. In the present application, a large amount of mesh fabric structure is used, and the orientation of the carbon fibers in the preform is weakened. The density is more uniform during the subsequent deposition and densification process, thereby avoiding the problem of uneven density distribution caused by excessive orientation of the carbon fibers. 2. In this application, the E-CVI method is combined. During the vapor deposition process, current is passed through the preform. In this way, a certain temperature gradient can be generated inside the preform, that is, the inner temperature is high and the outer temperature is low. In this way, the interior of the preform is preferentially deposited. As the deposition density increases, the preform deposition gradually grows from the inside to the outside to the final density. Not only is the deposition densification effect higher, but the finished product density is also higher and the density distribution is more uniform. Finally, the method provided in this application has a fast densification speed, and the density is ≥1.6g / cm after 100-200h of deposition. 3 ; A high-density carbon / carbon product is obtained, and the deposit is not easy to crust. The density difference coefficient at different positions is less than 2%, and the density distribution is more uniform. The carbon / carbon heater made in this way heats more evenly, and the deposited carbon is denser, and the service life of the heater is longer. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a schematic diagram of the preform structure in Example 1 of the present application; Figure 2 It is a schematic diagram of the E-CVI vapor deposition process principle in Example 1 of the present application. DETAILED DESCRIPTION

[0031] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0032] Example 1 A method for preparing a carbon / carbon heater for a single crystal thermal field comprises the following steps: S1, a preform having a structure of A / … / A / B / A / … / A is formed by stacking and needle punching carbon cloth and mesh tire cloth, such as Figure 1 As shown, A is mesh fabric, B is plain carbon fabric, and the surface density of mesh fabric is 100g / m 2 , the surface density of carbon cloth is 250g / m 2, B is in the center, A is symmetrically distributed on both sides of B, and the thickness of the preform is 40mm and the density is 0.2g / m 3 ; According to the structure of the heater, the preform is made into a required cylindrical or flat plate structure, and the heater blank is obtained by cutting to obtain the required outer contour of the heater; S2, the heater blank prepared in step S2 is subjected to E-CVI vapor deposition, combined with Figure 2 During the vapor deposition process, current is passed through the heater blank. In the E-CVI process, natural gas is used as the precursor, nitrogen is used as the dilution gas, the temperature in the deposition furnace is 850°C, and the nitrogen flow rate is 0.5m 3 / h, natural gas flow rate is 0.5m 3 / h, so that the center temperature of the mesh cloth of the heater blank reaches 1050℃, and the deposition ends after 150h. The density of the heater blank is 1.65g / cm 3 ; S3. Machining and finishing the heater blank after vapor deposition to obtain a carbon / carbon heater.

[0033] Example 2 A method for preparing a carbon / carbon heater for a single crystal thermal field comprises the following steps: S1, a preform having a structure of A / … / A / B / A / … / A is formed by stacking and needle punching carbon cloth and mesh tire cloth, such as Figure 1 As shown, A is mesh fabric, B is plain carbon fabric, and the surface density of mesh fabric is 70g / m 2 , the surface density of carbon cloth is 200g / m 2 , B is in the center, A is symmetrically distributed on both sides of B, and the preform is 30mm thick and 0.15g / m3 in density through the lamination of A mesh cloth. 3 ; According to the structure of the heater, the preform is made into a required cylindrical or flat plate structure, and the heater blank is obtained by cutting to obtain the required outer contour of the heater; S2, the heater blank prepared in step S2 is subjected to E-CVI vapor deposition, combined with Figure 2 During the vapor deposition process, current is passed through the heater blank. In the ECVI process, natural gas is used as the precursor, nitrogen is used as the dilution gas, the temperature in the deposition furnace is 800°C, and the nitrogen flow rate is 0.1m 3 / h, natural gas flow rate is 0.1m 3 / h, so that the center temperature of the mesh cloth of the heater blank reaches 1000℃, and the deposition ends after 100h. The density of the heater blank is 1.62g / cm 3 ; S3. Machining and finishing the heater blank after vapor deposition to obtain a carbon / carbon heater.

[0034] Example 3 A method for preparing a carbon / carbon heater for a single crystal thermal field comprises the following steps: S1, a preform having a structure of A / … / A / B / A / … / A is formed by stacking and needle punching carbon cloth and mesh tire cloth, such as Figure 1 As shown, A is mesh fabric, B is plain carbon fabric, and the surface density of mesh fabric is 150g / m 2 , the surface density of carbon cloth is 350g / m 2 , B is in the center, A is symmetrically distributed on both sides of B, and the density of the preform is 0.25g / m 3 ; According to the structure of the heater, the preform is made into the required cylindrical or flat structure, and the heater blank is obtained by cutting to obtain the required shape contour of the heater; S2, the heater blank prepared in step S2 is subjected to E-CVI vapor deposition, combined with Figure 2 During the vapor deposition process, current is passed through the heater blank. In the ECVI process, natural gas is used as the precursor, nitrogen is used as the diluent gas, the temperature in the deposition furnace is 900°C, and the nitrogen flow rate is 1m 3 / h, natural gas flow rate is 1m 3 / h, so that the center temperature of the mesh cloth of the heater blank reaches 1100℃. After 200h of deposition, the density of the heater blank is 1.67g / cm 3 ; S3. Machining and finishing the heater blank after vapor deposition to obtain a carbon / carbon heater.

[0035] Example 4 A method for preparing a carbon / carbon heater for a single crystal thermal field is carried out according to the method in Example 1, except that the preform preparation in step S1 specifically includes the following steps: 1) Preparation of modified phenolic resin: 15 kg of phenolic resin (alcohol-soluble thermosetting phenolic resin, specifically the phenolic resin of Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., CAS No. 9003-35-4) was mixed with 2 kg of silane coupling agent KH-550, and then 4 kg of mesophase asphalt and 0.8 kg of trioxymethylene were added after heating to 155° C., and stirred for 25 min. Then, 3 kg of glucose was added after cooling to 85° C., and the mixture was mixed and cooled to obtain a modified phenolic resin; 2) The modified phenolic resin and ethanol were mixed in a mass ratio of 1:9 to obtain a resin solution, and the mesh cloth and the carbon cloth were stacked according to the structure in Example 1 and then needle-punched and composited. During the needle-punching and composite process, the resin solution was sprayed at a spraying amount of 0.08 g / cm 2 After the needling, the preform is dried at 135°C to obtain a preform.

[0036] After the deposition in step S2 is completed, the density of the heater blank is 1.73 g / cm 3 .

[0037] Example 5 A method for preparing a carbon / carbon heater for a single crystal thermal field is carried out according to the method in Example 1, except that the preform preparation in step S1 specifically includes the following steps: 1) Preparation of modified phenolic resin: 10 kg of phenolic resin (alcohol-soluble thermosetting phenolic resin, specifically the phenolic resin of Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., CAS No. 9003-35-4) was mixed with 1 kg of silane coupling agent KH-550, and then 3 kg of mesophase asphalt and 0.5 kg of trioxymethylene were added after heating to 150° C., and stirred for 20 min. Then, 2 kg of sucrose was added after cooling to 80° C., and the mixture was mixed and cooled to obtain a modified phenolic resin; 2) The modified phenolic resin and ethanol were mixed in a mass ratio of 1:8 to obtain a resin solution, and the mesh cloth and the carbon cloth were stacked according to the structure in Example 1 and then needle-punched and composited. During the needle-punching and composite process, the resin solution was sprayed at a spraying amount of 0.05 g / cm 2 After the needling, the preform is dried at 120°C to obtain a preform.

[0038] A preform is obtained.

[0039] After the deposition in step S2 is completed, the density of the heater blank is 1.69 g / cm 3 .

[0040] Example 6 A method for preparing a carbon / carbon heater for a single crystal thermal field is carried out according to the method in Example 1, except that the preform preparation in step S1 specifically includes the following steps: 1) Preparation of modified phenolic resin: 20 kg of phenolic resin (alcohol-soluble thermosetting phenolic resin, specifically phenolic resin from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., CAS No. 9003-35-4) was mixed with 3 kg of silane coupling agent KH-550, and then 5 kg of mesophase asphalt and 1.2 kg of trioxymethylene were added after heating to 160° C., and stirred for 30 min. Then, 5 kg of glucose was added after cooling to 90° C., and the mixture was mixed and cooled to obtain a modified phenolic resin; 2) The modified phenolic resin and ethanol were mixed in a mass ratio of 1:10 to obtain a resin solution, and the mesh cloth and the carbon cloth were stacked according to the structure in Example 1 and then needle-punched and composited. During the needle-punching and composite process, the resin solution was sprayed at a spraying amount of 0.1 g / cm 2 After the needling, the preform is dried at 150°C to obtain a preform.

[0041] After the deposition in step S2 is completed, the density of the heater blank is 1.71 g / cm 3 .

[0042] Example 7 A method for preparing a carbon / carbon heater for a single crystal thermal field is carried out according to the method in Example 4, except that 1 kg of Peek is added in addition to glucose in step 1).

[0043] After the deposition in step S2 is completed, the density of the heater blank is 1.74 g / cm 3 .

[0044] Example 8 A method for preparing a carbon / carbon heater for a single crystal thermal field is carried out according to the method in Example 4, except that 3 kg of Peek is added in step 1) along with glucose.

[0045] After the deposition in step S2 is completed, the density of the heater blank is 1.72 g / cm 3 .

[0046] Comparative Example 1 A method for preparing a carbon / carbon heater for a single crystal thermal field is carried out according to the method in Example 1, except that in step S1, the preform is formed by alternatingly stacking mesh cloth and carbon cloth and needle punching, that is, the preform structure is an alternating structure of A / B / A... / B / A / ... / B / A.

[0047] After the deposition in step S2 is completed, the density of the heater blank is 1.58 g / cm 3 .

[0048] Comparative Example 2 A method for preparing a carbon / carbon heater for a single crystal thermal field is carried out according to the method in Example 1, except that the preform is made by stacking and needle-punching a mesh cloth. After the deposition in step S2 is completed, the density of the heater blank is 1.45 g / cm 3 .

[0049] Comparative Example 3 A method for preparing a carbon / carbon heater for a single crystal thermal field is carried out according to the method in Example 1, except that a conventional CVI process is used in step S2, no current is passed through the heater blank, the temperature in the deposition furnace is 1050°C, and the density of the heater blank after the deposition in step S2 is 1.03 g / cm 3 .

[0050] Performance Testing The product density was measured at different positions of the heater after the deposition in step S2 in Example 1, and the results are shown in Table 1 below.

[0051] Table 1: In Example 1, after the deposition in step S2 is completed, the density difference in the thickness direction is 0.05 g / cm 3 The density fluctuation in the thickness direction of the heater is small, the deposition is more uniform, and the quality of the deposition and the stability and consistency of the performance are improved. In addition, the average value in Table 1 above is 1.648518519, the standard deviation is 0.016262591, and the coefficient of variation (that is, the ratio of the standard deviation to the mean value, used to quantify the degree of dispersion of the data) is <1.5%.

[0052] In addition, the above statistics are performed on the density range (the difference between the maximum and minimum density in the thickness direction) and the coefficient of variation after the deposition in step S2 in the remaining embodiments and comparative examples, and the statistical results are shown in Table 2 below.

[0053] Table 2: Referring to the test results in Tables 1 and 2 above, it can be seen that the use of the preform structure in the present application in conjunction with the E-CVI process makes the deposition on the preform more uniform, the density difference at different positions of the product is small, and the density distribution is more uniform. Combined with the test results of Comparative Example 1, when the preform is alternately distributed with mesh cloth and carbon cloth, due to the strong orientation of the carbon cloth, the carbon fibers are arranged in a specific direction, resulting in a faster penetration rate of carbon atoms in certain directions and slower penetration rate in other directions during the deposition and densification process, resulting in a uniform density distribution. Therefore, the present application uses carbon cloth in the center and mesh cloth symmetrically distributed on both sides. The orientation of the carbon fibers in the preform is greatly weakened, so that the carbon atoms penetrate more evenly during the deposition process, and no density gradient is formed, and the density distribution is more uniform.

[0054] Combined with the test results in comparative example 2, when all mesh cloth layers are used for needle punching, the uniformity of its deposition is reduced. The presence of carbon cloth not only helps to improve the strength, but more importantly, the carbon cloth at the center of the present application also provides good electrical conductivity and thermal conductivity. The carbon cloth at the center can more effectively transfer current and heat during vapor deposition, making the temperature distribution during deposition more uniform. The high porosity of the mesh cloth in comparative example 2 will lead to inconsistent carbon penetration speed during deposition, which will affect the uniformity of the deposited layer. In addition, there is a lack of carbon cloth layers with good electrical conductivity in comparative example 2. The uneven temperature distribution during deposition will also lead to uneven deposition, and the deposition efficiency is also reduced. Combined with the test results of comparative example 3, when the traditional CVI deposition process is used, the density difference in the thickness direction is large.

[0055] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a carbon / carbon heater for a single crystal thermal field, characterized in that: The steps include: S1, cutting a preform made of a mesh cloth and a carbon cloth to form a heater blank, wherein the preform is made of a layer of carbon cloth and a plurality of mesh cloths symmetrically arranged on both sides of the carbon cloth; S2, vapor deposition is performed on the heater blank prepared in step S2, and current is passed through the heater blank during the vapor deposition process, so that the center temperature of the mesh cloth of the heater blank reaches 1000-1100°C, and the deposition is completed after 100-200 hours, and the density of the heater blank is ≥1.6g / cm 3 ; S3. Machining and finishing the heater blank after vapor deposition to obtain a carbon / carbon heater.

2. The method for preparing a carbon / carbon heater for a single crystal thermal field according to claim 1, characterized in that: In step S1, the number of layers of the web tire cloth is 2-10.

3. The method for preparing a carbon / carbon heater for a single crystal thermal field according to claim 1, characterized in that: The surface density of the mesh fabric in step S1 is 70-150g / m 2 , the surface density of carbon cloth is 200-350g / m 2 .

4. The method for preparing a carbon / carbon heater for a single crystal thermal field according to claim 1, characterized in that: The density of the preform in step S1 is 0.15-0.25 g / m 3 .

5. The method for preparing a carbon / carbon heater for a single crystal thermal field according to claim 1, characterized in that: The vapor deposition parameters in step S2 are: natural gas as the precursor, nitrogen as the diluent gas, the temperature in the deposition furnace is 800-900°C, and the nitrogen flow rate is 0.1-1m 3 / h, natural gas flow rate is 0.1-1m 3 / h, the deposition time is 100-200h.

6. The method for preparing a carbon / carbon heater for a single crystal thermal field according to claim 1, characterized in that: In step S1, the preform is made by connecting the mesh cloth and the carbon cloth, and the mesh cloth and the mesh cloth by needle punching.

7. The method for preparing a carbon / carbon heater for a single crystal thermal field according to claim 1, characterized in that: In step S1, modified phenolic resin is sprayed when the preform mesh cloth and carbon cloth, and the mesh cloth and mesh cloth are compounded by needle punching, and baking is performed after the needle punching compounding is completed.

8. The method for preparing a carbon / carbon heater for a single crystal thermal field according to claim 7, characterized in that: The modified phenolic resin is prepared by mixing the following raw materials in parts by weight: 10-20 parts of phenolic resin, 3-5 parts of mesophase asphalt, 1-3 parts of silane coupling agent, 2-5 parts of sucrose or glucose, and 0.5-1.2 parts of trioxymethylene.

9. The method for preparing a carbon / carbon heater for a single crystal thermal field according to claim 7, characterized in that: The preparation of the preform in step S1 specifically includes the following steps: The mesh cloth and the carbon cloth are stacked and then needle-punched for compounding. During the needle-punching process, a resin solution of modified phenolic resin and ethanol mixed in a mass ratio of 1: (8-10) is sprayed. After the needling is completed, the preform is dried at 120-150°C to obtain a preform.

10. A single crystal carbon / carbon heater for thermal field prepared by the preparation method as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Carbon / carbon compound material heating element and production technology thereof

    CN101386547B

  • Gas phase rapid preparation method of U-type carbon / carbon heat-generating body

    CN104710184A

  • A carbon / carbon composite heating element with a pyrolytic carbon coating on its surface and its preparation method.

    CN108975922B

  • Rapid preparation method of carbon-carbon heating body

    CN117510219A

  • Carbon-carbon composite material as well as preparation method and application thereof

    CN117586037A